2018
DOI: 10.1017/jfm.2018.466
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of wind turbulence over breaking waves

Abstract: We study wind turbulence over breaking waves based on direct numerical simulation (DNS) of two-fluid flows. In the DNS, the air and water are simulated as a coherent system, with the interface captured using the coupled level-set and volume-of-fluid method. Because the wave breaking is an unsteady process, we use ensemble averaging over 100 runs to define turbulence statistics. We focus on analysing the turbulence statistics of the airflow over breaking waves. The effects of wave age and wave steepness are inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 119 publications
0
44
0
Order By: Relevance
“…The laboratory work of Saket et al (2018) showed that B th ≈ 0.85 also segregates breaking from nonbreaking crests in the presence of wind forcing in deep water breaking. A number of high-fidelity two-phase flow simulations of breaking waves in the presence of wind forcing (e.g., Tang et al, 2017;Yang et al, 2018) have been recently performed. Detailed quantification of the effect of direct wind forcing on the proposed breaking onset criterion in shallow water is left for future study.…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory work of Saket et al (2018) showed that B th ≈ 0.85 also segregates breaking from nonbreaking crests in the presence of wind forcing in deep water breaking. A number of high-fidelity two-phase flow simulations of breaking waves in the presence of wind forcing (e.g., Tang et al, 2017;Yang et al, 2018) have been recently performed. Detailed quantification of the effect of direct wind forcing on the proposed breaking onset criterion in shallow water is left for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Our measurements or analysis were not equipped and did not make any special provisions to deal with these instances any differently than other cases. In terms of the airflow separation, this can be of relatively low importance, based on the fact that short wave breaking (or even spilling breaking) is not expected to significantly impact the airflow pattern over the dominant wave (Yang et al, ). However, there is no doubt that these small breakers impose some additional vortex force near the surface, as well as dissipate their energy through breaking, and thus make an impact on the turbulence investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve site-specific optimal wind farm design and operation [86,87], further research from both fundamental and applied points of view needs to be carried out. Such work should focus, among others, on: (1) the role and interaction of the two wake meandering mechanisms for different turbine operational and atmospheric conditions; (2) the physics and models for wake meandering in complex terrain, under offshore conditions with breaking waves [88] and in coastal areas [89]; and (3) extension of the meandering models to the wake of marine and hydrokinetic energy devices (may be of complex configuration [90]) interacting with sediment transport [91,92] and different types of turbulent eddies [93,94].…”
Section: Discussionmentioning
confidence: 99%